2017
DOI: 10.15376/biores.12.3.5417-5427
|View full text |Cite
|
Sign up to set email alerts
|

Fire Properties of Pinus densiflora Utilizing Fire-retardant Chemicals based on Borated and Phosphorus (I) – Combustion Characteristics

Abstract: The combustion and thermal characteristics of fire retardant-treated pine (Pinus densiflora) were evaluated according to the KS F ISO 5660-1 (2003) standard, using a cone calorimeter. The specimens were treated with fire-retardant chemical compounds using pressure-impregnation equipment to reliably impregnate the compounds inside the wood. The heat release rate value of the fire retardant-treated wood specimens showed that the heat release time was delayed. A reduction of the total heat release value can indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Figure 1 shows two types of untreated and FRC-treated specimens (Fire retardant treated wood by pressure-treatment; FRTW-pressure specimens). In the previous study (Seo et al 2017), it was concluded that pressurizing FRCs was more effective in improving the fire retardant performance of wood. Therefore, in this paper, the experiment was conducted to compare FRTW-pressure and untreated test specimens.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Figure 1 shows two types of untreated and FRC-treated specimens (Fire retardant treated wood by pressure-treatment; FRTW-pressure specimens). In the previous study (Seo et al 2017), it was concluded that pressurizing FRCs was more effective in improving the fire retardant performance of wood. Therefore, in this paper, the experiment was conducted to compare FRTW-pressure and untreated test specimens.…”
Section: Methodsmentioning
confidence: 95%
“…The test specimens were reduced to 2 mm to 4 mm in size after the cone calorimeter test. The chemical compositions of the FRCs were the same as the previously conducted study (Seo et al 2017). Table 1 shows the composition of the fire retardant chemicals (FRCs) used in this study and the formula of the ingredient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1)에 의해 산정된   는 시료의 독성지수 산출 계산식 에 적용된다. (Seo et al, 2017;Liang and Ho, 2007;Lowden and Hull, 2013 (Cho et al, 2012;Boningari and Smirniotis, 2016;Huang et al, 2017)이므로 화재 위험성 평가 시 고려가 필요한 부분으로 사료된다.…”
Section: 서 론unclassified